Artificial Ventilation A Basic Clinical Guide - Baker, David J. (Springer International Publishing : Imprint: Springer, 2016)
This book provides a basic clinical guide to the principles and practice of artificial ventilation, both manual and mechanical. It covers the development of artificial ventilation through the ages and the essential anatomy and physiology behind it. While there are many detailed texts available on mechanical ventilation, they are usually aimed at the hospital specialist and cover the many complex modes of ventilation used in the hospital setting. This book covers the basics of airway and ventilation management for  non-specialists working in pre-hospital and emergency medicine. It fulfils the need for a resource that explains simply and clearly basic respiratory physiology, the pathophysiology behind respiratory failure and the practical aspects of artificial ventilation. This book links the two areas of hospital and pre-hospital practice together to promote better understanding of artificial ventilation by medical, paramedical and nursing  personnel working in different fields of medicine.  .